Consistency of Targeted Metatranscriptomics and Morphological Characterization of Phytoplankton Communities - Vuorio, Kristiina; Mäki, Anita; Salmi, Pauliina; Aalto, Sanni L.; Tiirola, Marja (Frontiers in Microbiology, 2020)
Phytoplankton community composition is the basis for environmental monitoring and status assessment of aquatic ecosystems. Phytoplankton community composition studies have been based on time-consuming and expertise-demanding light microscopy analyses. Molecular methods have potential in replacing microscopy, but the high copy number variation in ribosomal genes and the lack of universal primers for simultaneous amplification of prokaryotic and eukaryotic genes complicate the data interpretation. Primer-independent methods focusing on ribosomal RNA (rRNA) could be a preferred basis for phytoplankton studies. We applied a directional high throughput sequencing (HTS) approach, previously developed by us, to analyze 16S and 18S rRNA community structures. Comparison of 83 boreal lake samples showed that the relative class level abundances of eukaryotic phytoplankton and order level abundances of cyanobacteria in the HTS data were consistent with the microscopy results. The list of genera had low correspondence, mainly due to lack of reference library sequences. HTS was superior in differentiating genera lacking morphological characteristics that are extensively represented in the reference databases. Targeted metatranscriptomics showed a feasible method to replace microscopy but may require direct indexing of sequences to their environmental indicator values without linking them to named species, as comprehensive databases of eukaryotic species and their molecular barcodes are still lacking.